2016
DOI: 10.1589/jpts.28.3105
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation patterns in acceleration-based phases during reach-to-grasp movement

Abstract: [Purpose] An earlier study divided reaching activity into characteristic phases based on hand velocity profiles. By synchronizing muscle activities and the acceleration profile, a phasing approach for reaching movement, based on hand acceleration profiles, was attempted in order to elucidate the roles of individual muscle activities in the different phases of the acceleration profile in reaching movements. [Subjects and Methods] Ten healthy volunteer subjects participated in this study. The aim was to electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
4
3
0
Order By: Relevance
“…The patterns of phasic muscle activations presented in this study are coherent with precedent findings in literature ( Tokuda et al., 2016 ), ( Sabatini, 2002 ). The activity of deltoid anterior (DA) during the acceleration phase is not surprising; on the contrary, we also found increased activity of the DA in the deceleration phase most likely as a response to the increased activity of the antagonist muscle (posterior deltoid) used to decelerate the limb ( Tokuda et al., 2016 ). This response is most likely a strong co-contraction that is needed for the deceleration phase to stop and stabilize the limb ( Kornecki et al., 2001 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The patterns of phasic muscle activations presented in this study are coherent with precedent findings in literature ( Tokuda et al., 2016 ), ( Sabatini, 2002 ). The activity of deltoid anterior (DA) during the acceleration phase is not surprising; on the contrary, we also found increased activity of the DA in the deceleration phase most likely as a response to the increased activity of the antagonist muscle (posterior deltoid) used to decelerate the limb ( Tokuda et al., 2016 ). This response is most likely a strong co-contraction that is needed for the deceleration phase to stop and stabilize the limb ( Kornecki et al., 2001 ).…”
Section: Discussionsupporting
confidence: 92%
“…The upper trapezius (UT) presented great activity in the initial phase of the movement but did not cease its contribution in the deceleration phase, acting as a phasic and anti-gravity muscle. This was previously reported in a reach to grasp study where the EMG was obtained by decomposing the movement in phases using the acceleration, highlighting the anti-gravity role of the upper trapezius ( Tokuda et al., 2016 ). While many applications consider DA as the main shoulder elevator, we found that UT play this role in a major extent in the accelerating phase ( Sabatini, 2002 ).…”
Section: Discussionsupporting
confidence: 67%
“…This is in contrast to the experiments conducted by the Flanders group (Buneo et al, 1994, 2008; Flanders et al, 1991, 1992, 1996) where a pointing protocol with elbow rotations was involved. The important role played by the trapezius muscle for modulation in both directions is in agreement with reports by other groups that along with the anterior deltoid, it plays an important role in shoulder orientation for pointing direction (Tokuda et al, 2016; Sabatini et al, 2002). It should be noted that none of the differences in contribution to classification here is due to differences in EMG amplitude as this variable is normalized (see Methods).…”
Section: Resultssupporting
confidence: 92%
“…In contrast to the two afore-mentioned muscles, the phasic activity of the medial and posterior deltoids are more tuned for downward pointing, showing higher accuracies for distinguishing downward pointing angles. The importance of all these muscles in pointing have been highlighted by various studies [Flanders, 1991, Flanders et al, 1994, Flanders et al, 1996, Mira et al, 2021, Tokuda et al, 2016]. In contrast to the previous studies, the use of classification accuracy allows for a greater ease in comparing and contrasting the roles of individual muscles.…”
Section: Discussionmentioning
confidence: 99%